3,4-Diaminopyridine facilitates norepinephrine release in chick sympathetic neurons - HUANG Hua-yu; ZHOU Cheng-wen (Acta Pharmacologica Sinica; Vol 16, No 4 (July 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism by which 3,4-diaminopyridine (DAP) facilitates electrically evoked [3H]norepinephrine ([3H]NE) release in sympathetic neurons from chick embryos. METHODS: The neurons were incubated with [3H]NE or Fura-2. [3H]NE) release or [Ca2+]i was determined. RESULTS: The electrically evoked [3H]NE release and the elevation of [Ca2+]i were inhibited completely by sodium channel blocker tetrodotoxin (TTX), strongly by the antagonist of N-type calcium channel omega-conotoxin GVIA (CTX), and slightly by the antagonist of L-type calcium channel (-)isradipine, but enhanced by the agonist of L-type calcium channel Bay k 8644. In the presence of DAP, the electrically evoked [3H]NE release and [Ca2+]i were facilitated, the inhibition of [3H]NE release and [Ca2+]i by CTX was attenuated, but that by (-)isradipine was enhanced, and Bay k 8644 was no longer effective. CONCLUSION: In the cultured chick sympathetic neurons DAP facilitates electrically evoked [3H]NE release mediated by enhancement of influx of external Ca2+ through the L-type Ca2+ channel.